MANAGERIAL COMPETENCE OF SCHOOL PRINCIPAL PERFORMANCE IN TULANG BAWANG DISTRICT, LAMPUNG PROVINCE IN 2022 - Marzius Insani; Wina Astuti; Risma Margaretha Sinaga; Undang Rosidin; Sowiyah Sowiyah; Hasan Hariri (Universitas Labuhanbatu, 2023)
This study aims to comprehensively reveal the competence of school principals in Tulang Bawang Regency. This research is a case study research in the field using an analytical perspective. This field research is a collaboration with school supervisors to obtain accurate and reliable data. It was concluded that the highest managerial competence of the principals of SMP in Tulang Bawang Regency was SMP Yapindo with a score of 3.89 followedby SMPN 2 Banjar Agung with a score of 3.86, SMPN 3 Menggala with a score of 3.8, SMPN Satap 2 Gedung Meneng with a score of 3.26, SMP Dwipa Karya Mandiri with a score 3.23, Menggala 4 Middle School with a score of 3.14, Angkasa Middle School with a score of 3.03, Meneng Satap 1 Middle School with a score of 2.87, and the lowest was obtained by Satap 3 Meneng Building Middle School. The average performance of school principals in managerial competence is 3.30. This means that the performance of school principals is classified as good. Key words: Principal, Junior high, Competency, Managerial.Abstrak Penelitian ini bertujuan untuk mengungkap secara komprehensif kompetensi kepala sekolah di Kabupaten Tulang Bawang. Penelitian ini adalah penelitian studi kasus di lapangan dengan menggunakan perspektif analitik. Penelitian lapangan ini merupakan kolaborasi dengan pengawas sekolah guna mendapatkan data yang akurat dan dapat dipercaya. Disimpulkan bahwa kompetensi manajerial kepala sekolah SMP Se-Kabupaten Tulang Bawang tertinggi adalah SMP Yapindo dengan skor 3.89 diikuti SMPN 2 Banjar Agung dengan skor 3.86, SMPN 3 Menggala dengan skor 3.8, SMPN Satap 2 Gedung Meneng dengan skor 3.26, SMP Dwipa Karya Mandiri dengan skor 3.23, SMP 4 Menggala dengan skor 3.14, SMP Angkasa dengan skor 3.03, SMPN Satap 1 Gedung Meneng dengan skor 2.87, dan terendah didapat oleh SMPN Satap 3 Gedung Meneng. Rata-rata kinerja kepala sekolah pada kompetensi manajerial adalah 3.30 ini berarti bahwa kinerja kepala sekolah tergolong Baik.Kata kunci: Kepala sekolah, SMP, Kompetensi, Manajerial